1997
DOI: 10.1364/josaa.14.002033
|View full text |Cite
|
Sign up to set email alerts
|

Variations in photoreceptor directionality across the central retina

Abstract: Cones show a differential sensitivity to light coming from different portions of the pupil, typically being most sensitive to light from the center of the pupil. We measured the directional properties of the cones across the central 6 deg of the retina, using an optical imaging technique. We find that the cones in the center of the fovea have the broadest tuning. The width of the angular tuning changes rapidly from 0 deg to 1 deg retinal eccentricity, with cones at 1 deg being much more narrowly tuned than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 31 publications
8
53
2
Order By: Relevance
“…Burns et al 9 showed that values changed rapidly with retinal eccentricity, with the width of the pupil intensity distribution being broader at the center of the fovea than at higher eccentricities. We measured as a function of retinal eccentricity (0 deg and 0.5, 1, 2, and 3 nasal and temporal) for 543 nm and compared the results with the predictions from the simulation.…”
Section: Variation Of With Retinal Locationmentioning
confidence: 99%
See 3 more Smart Citations
“…Burns et al 9 showed that values changed rapidly with retinal eccentricity, with the width of the pupil intensity distribution being broader at the center of the fovea than at higher eccentricities. We measured as a function of retinal eccentricity (0 deg and 0.5, 1, 2, and 3 nasal and temporal) for 543 nm and compared the results with the predictions from the simulation.…”
Section: Variation Of With Retinal Locationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The principal aim of these techniques is to provide objective information on a given aspect of the visual system rapidly and reliably and in a manner that is well tolerated by both normal subjects and patients. Generally, one can get the same information with traditional psychophysical techniques, but the reliability and time saving of the objective techniques make it desirable for eventual clinical purposes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the photoreceptor reflectance fluctuations [11,41,42] and other sources of variability such as image registration, tear film and subject alignment, the observed reflectance amplitude values (shown in Table 2 ) are consistent with the SCE predictions. Table 2 Measured relative average image intensities for images collected with constant PMT gain compared against predicted values (in parenthesis) according to the SCE measured objectively at fixation (ρ = 0.11 mm ) [43]. A Gaussian intensity ...…”
Section: Figmentioning
confidence: 99%